PANDANGAN HUKUM PIDANA ISLAM DALAM PEMBERITAAN HOAX - Munadi Munadi (ASASI: Journal of Islamic Family Law, 2021)
The spread of hoax news is an act of violating the law of article 28 paragraph 1 of Law Number 11 of 2008 concerning ITE, and criminal sanctions for hoax news spreaders are contained in article 45 paragraph 1, namely the maximum imprisonment is six years and / or a maximum fine of one billion rupiah. In Islam, telling lies, lying, prejudice or slandering is not justified. Islam encourages its followers to always speak honestly, objectively and speak the truth. In Islamic criminal law, someone who has spread fake news (hoax) will get ta'zir punishment in the form of an unlimited prison sentence. Sentenced to confinement until he repents and either personally or until he dies.